Evangelización y culturas. : Aportaciones pastorales desde “Gaudium et spes” (Estudio Agustiniano, 2013)
Following the council method, the formulated truth has not been the point of starting of this meditation, if not the signs of the time and particularly two of them connected each other: the globalization and pluralism. These signs, illuminated by divine mercy, take us to try new attitudes, processes, and pastoral projects. I explain some keys of pastoral action which are both at the same time memories and a development of which is suggested in Pastoral constitution “Gaudium et spes”. They are learned and shared keys on the own pastoral experience, in prayer meetings and training workshop and pastoral study with other priests: Church sign of universal fraternity. Poor Church, at the service of the poor and those who suffer; the good news proclaimed, above all, by means of the testimony; witness spirituality.